The Effects of Tragacanth Addition on the Thermal and Mechanical Properties of Lightweight Concretes Mixed with Expanded Clay - Devecioglu, Atilla Gencer; Bicer, Yasar (Budapest Univ Technology Economics, 2016)
The effects of adding tragacanth, which is a natural resin, as expanded clay aggregate and binder to specimens on the thermal and mechanical properties of lightweight concretes has been examined in this study. Expanded clay with diameters of 4-8mm and by proportion 5%, 10% and 20% of cement's weight was added to specimens in the study. As a binder, by addition of 1% tragacanth to cement at the rate of 1%, new lightweight concrete specimens with densities varying between 867 kg/m(3) to 1452 kg/m(3) were produced. Tragacanth with the same proportions of mixture was prepared in pure specimens in order to compare. Water/cement ratio was kept constant in all mixtures. At the end of a drying time of 28 days, thermal conductivity, specific heat capacity, compressive strength, modulus of elasticity, water absorption and drying quantities of specimens were confirmed. As a result, decrease of thermal conductivity, density and compressive strength of specimens was seen through adding tragacanth and raising the amount of expanded clay.
Keywords: Expanded clay; tragacanth; thermal conductivity; lightweight concrete